Thematic analysis in two poems written by Dylan Thomas - Mahmood, Wafa Salim (Journal of Humanities & Social Sciences, 2017)
The research attempts a thematic analysis in two poems written by Dylan Thomas, an English modern poet, novelist and playwright. It deals with the way that Thomas used to present the theme of death in two poems of Dylan Thomas. Thus, the aim is to attain how Dylan Thomas could describe death as a character in his poems:"A Refusal to Mourn the Death, by Fire, of a Child in London," one of Thomas’s more accessible poems that will be undertaken, illustrates well the almost sacramental view of nature that characterizes this later poetry. In, "And Death Shall Have no Dominion", for it is especially in this poem that he expresses his wide and deep love of humanity and the immortality of the sentiment that death shall never triumph over life.